Teacher deliberation within the context of Singaporean curricular change: pre- and in-service PE teachers' perceptions of outdoor education. Issue 3 (2nd July 2016) - Atencio, Matthew; Tan, Yuen Sze Michelle
ABSTRACT: The study featured in this paper investigates pre- and in-service Physical Education (PE) teachers' diverse views of OE (Outdoor Education) against the backdrop of numerous curricular changes underpinning Singaporean education. We highlight the potential challenges Singaporean schools and teachers may face in implementing the newly formalized OE curriculum. Findings revealed the teachers' prioritization of high elements and adventure activities within residential camps. Then, the teachers linked these 'risky' and 'unfamiliar' activities with transferrable learning outcomes, mostly in line with students' personal and social development. The more experienced teachers in the cohort tended to advocate that OE could be situated within local school and community environs. Yet, this envisioning of OE within a place-based learning model reflected limited understanding of this concept. We conclude by suggesting that curriculum designers and teacher educators should draw upon pre- and in-service PE teachers' perceptions of OE. It is imperative that these teachers' key concerns and beliefs, which currently structure their work in this recently formalized subject area, are used to contextualize the extensive curricular change and professional learning endeavors that are being implemented by the education ministry.